Beyond Distinction–Based Narratives. Interior Design's Educational History as a Knowledge Base. Issue 4 (December 2021) - Vanhee, Sam; Vandevoort, Benoît; Floré, Fredie; De Vos, Els
In this article, we look into different texts treating the history of education of interior design. Ever since the interior design discipline has started to seek connection with academia, research on its past has become a negotiation scene for a shared understanding of the discipline, its roots, and its current practice. Academic discourse is characterized by a need to counter perceptions that have pestered the discipline in the past, and have hindered its process toward professionalization. By scanning through the body of theory that has been produced in the past two decades, we search for content that acknowledges the value of historical education and its contribution to a debate on the discipline's identity. After contextualizing this specific kind of research, we not only try to find common ground between different texts that each focus on a specific time period, school, or country, but also aim to unveil the position taken by an author when constructing such a history. All authors showcase a need to use their text as a confirmation of disciplinary distinction—an aspect heavily perpetuated throughout discourse on interior design's identity. To conclude, we propose a different perspective on educational history that transcends a distinction–based narrative by postulating interior design's educational history as a strategy to produce new knowledge.